O fantástico em Aluísio Azevedo e Coelho Neto: análise dos contos Demônios e A Bola - GOMES, Lívia Fernanda Diniz (2018)
The short stories Demônios (1893) by Aluísio Azevedo and A Bola (1927) by Coelho Neto are the objects of study of the analysis in this dissertation that aims to legitimitize these works as fantastics through its fundamental characteristics, formal procedures and innate themes of the fantastic literature.To this end, the theoretical contributions by French theorists Lois Vax (1965), Roger Caillois (1966), Irène Bessière (1974), the French-Bulgarian critic Tzvetan Todorov (2012), the Portuguese theorist Filipe Furtado (1980), the Italian critic Remo Ceserani (2004) and the Catalan professor David Roas (2014) will be used. Although these are short stories by authors who lived in the context of Rio's tropical Belle époque (acquaintanceship included), the uncanny is presented differently in each one of them, due to the different strands of fantastic to which the works belong to, as defined by the Italian writer Italo Calvino (2004): Demônios (1893), the visionary fantastic and A Bola (1927), the everyday fantastic. Both present the ambiguity which comes from the hesitation (or astonishment, doubt or uncertainty), the result of the conflict between reality and supernatural, everyday reality and unusual atmosphere, natural and extraneous explanation. The relation with the reader’s experience of reality, for purposes of verisimilitude effect, and the choice for the use of self-digetic narrator appear as points of approximation of the two stories. On the other hand, the representations of time and space, as well as the main themes addressed in each story, exemplify the marked differences between the two works. The choice to work on these stories is due to the fact that they have remained forgotten by critics and the public, receiving little attention in the bibliographies and studies about Aluísio Azevedo and Coelho Neto, authors widely known in the Brazilian literary tradition, but in general, are not associated with the aesthetics of the fantastic because are linked to other literary moviments. Moreover, the fantastic Brazilian literature is still little publicized, known and studied in academic circles.